1997
DOI: 10.2134/agronj1997.00021962008900030011x
|View full text |Cite
|
Sign up to set email alerts
|

Kill Date of Vetch, Rye, and a Vetch—Rye Mixture: II. Soil Moisture and Corn Yield

Abstract: Spring cover crop kill date effects on N and water availability to subsequent no‐till corn (Zea mays L.) have not been studied. This 2‐yr study was conducted in 1990 and 1991 at Coastal Plain and Piedmont locations in Maryland to evaluate soil moisture and corn responses to three cover crop kill dates, three corn planting dates, and four fertilizer N (FN) rates following cover crops of hairy vetch (Vicia villosa Roth), cereal rye (Secale cereale L.), and vetch‐rye mixture. No‐cover checks were included for eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
99
1
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(117 citation statements)
references
References 19 publications
15
99
1
2
Order By: Relevance
“…The bare soil simulated drainage was on average 60.7 mm year -1 larger than the drainage of the CC treatment, but this difference reached 188 mm in very rainy years as 2009/10. These results support previous research on CCs that concluded that good management of the CC would not lead to water competition with the subsequent cash crop even during dry years as 2007 and 2011 (Clark et al, 1997;Alonso-Ayuso et al, 2014). Moreover, this result supported the theory that CCs not only 25 reduce leaching of nitrate and other solutes but also reduce intensive drainage (Thorup-Kristensen et al, 2003).…”
Section: Water Balance Analysissupporting
confidence: 89%
“…The bare soil simulated drainage was on average 60.7 mm year -1 larger than the drainage of the CC treatment, but this difference reached 188 mm in very rainy years as 2009/10. These results support previous research on CCs that concluded that good management of the CC would not lead to water competition with the subsequent cash crop even during dry years as 2007 and 2011 (Clark et al, 1997;Alonso-Ayuso et al, 2014). Moreover, this result supported the theory that CCs not only 25 reduce leaching of nitrate and other solutes but also reduce intensive drainage (Thorup-Kristensen et al, 2003).…”
Section: Water Balance Analysissupporting
confidence: 89%
“…Krueger et al (2011) reported that soil moisture after termination of rye cover crop did not differ from their control plots when rye production was less than 900 kg ha -1 (804 lb ac -1 ) in Minnesota. Similarly, Clark et al (1997aClark et al ( , 1997b) also reported that soil moisture after termination of rye cover crop did not differ from their control plots for rye biomass production up to 2,919 kg ha -1 (2,607 lb ac -1 ) in the Piedmont of Maryland during the severe drought of 1991. However, Clark et al (1997aClark et al ( , 1997b) also reported that soil moisture was significantly greater during 15 of the 27 weekly measurements made when rye biomass production was 3,935 and 2,330 kg ha -1 (3,514 and 2,081 lb ac -1 ) in the Coastal Plains of Maryland during 1990 and 1991, in which precipitation was relatively similar to the 20-year mean precipitation.…”
Section: Figurementioning
confidence: 87%
“…In addition, the presence of plant tissue surface area above the soil surface increases the potential for dew formation and potential stem flow to the soil surface if enough water vapor is condensed on plant tissues. The mulch effect, potential enhancement of dew formation, and in the long term any increases in soil water holding capacity due to increases in soil organic matter content, could potentially increase antecedent soil water availability to emerging and young cash crop (Mulumba and Lal 2008;Clark et al 1997b;Waggner and Mengel 1988;Moschler et al 1967). Therefore, given the numerous and potentially opposing effects cover crops may have on soil moisture and corresponding effects on the following cash crop, our objective was to quantify potential differences in soil moisture due to the presence of a rye cover crop in a corn-soybean rotation at various locations in the midwestern United States during the drought of 2012.…”
mentioning
confidence: 99%
“…Por outro lado, quando cultivado sobre resíduos de aveia preta, foram observadas as maiores respostas ao N aplicado no milho. Isto foi atribuído à menor disponibilidade de N no solo após aveia preta, possivelmente pela imobilização de N ocorrida no Diversos autores evidenciaram que, sem aplicação de adubação nitrogenada, a produtividade de grãos de milho cultivado em sucessão aos sistemas consorciados de espécies leguminosas e gramíneas como cobertura de solo foi maior do que a obtida em sucessão a coberturas de gramíneas em cultivo isolado (Beutler et al, 1997;Clark et al, 1997b;Vaughan & Evanylo, 1998 matéria seca da cobertura de solo em relação ao cultivo isolado de aveia.…”
Section: Produtividade De Grãos De Milhounclassified